Shopping, money, and higher values - Cicovacki, Predrag (Array, 2019)
In our consumerist world, our sense of values centers around the possession of money and the possibility of buying things we have never imagined we need. Shopping has become our lifestyle and even our sense of freedom seems to reduce to a choice between the brands. I examine this state of affairs from three perspectives: apologetic, critical, and one attempting to balance our obsession with money with a proper understanding of higher values. Following Nicolai Hartmann, I attempt to explain, defend, and further develop the last of these standpoints.